The bone tree eaudiobook A novel. - Iles, Greg (Penn Cage, 2015)
Don't miss the latest Natchez Burning novel, SOUTHERN MAN From #1 New York Times bestselling author Greg Iles comes the second novel in his Natchez Burning trilogy—which also includes Natchez Burning and the upcoming Mississippi Blood—an epic trilogy of blood and race, family and justice, featuring Southern lawyer Penn Cage. Former prosecutor Penn Cage and his fiancée, reporter and publisher Caitlin Masters, have barely escaped with their lives after being attacked by wealthy businessman Brody Royal and his Double Eagles, a KKK sect with ties to some of Mississippi's most powerful men. But the real danger has only begun as FBI Special Agent John Kaiser warns Penn that Brody wasn't the true leader of the Double Eagles. The puppeteer who actually controls the terrorist group is a man far more fearsome: the chief of the state police's Criminal Investigations Bureau, Forrest Knox. The only way Penn can save his father, Dr. Tom Cage—who is fleeing a murder charge as well as corrupt cops bent on killing him—is either to make a devil's bargain with Knox or destroy him. While Penn desperately pursues both options, Caitlin uncovers the real story behind a series of unsolved civil rights murders that may hold the key to the Double Eagles' downfall. The trail leads her deep into the past, into the black backwaters of the Mississippi River, to a secret killing ground used by slave owners and the Klan for over two hundred years . . . a place of terrifying evil known only as "the bone tree." The Bone Tree is an explosive, action-packed thriller full of twisting intrigue and deadly secrets, a tale that explores the conflicts and casualties that result when the darkest truths of American history come to light. It puts us inside the skin of a noble man who has always fought for justice—now finally pushed beyond his limits. Just how far will Penn Cage, the hero we thought we knew, go to protect those he loves?